Nuclear factor E2-related factor 2’s activation in transgenic mice fed with dosage of saturated or unsaturated fatty acids using in vivo bioluminescent imaging (International Journal of Health, Animal Science and Food Safety, 2017)
To counteract oxidative stress cells developed several mechanisms, including the transcription factor Nuclear Factor E2-related factor 2 (Nrf2). The aim of the study was to evaluate the activation of Nrf2 in transgenic mice fed saturated or polyunsaturated fatty acids and the anti-inflammatory effect of estrogens on organism. Forty-eight ARE CRE OMO reporter mice were divided into 3 groups, consisting of 16 animals, based on presence/absence of estrogens (ovariectomized or sham female, OVX - SH; male, MA). Each group was further split in 4 subgroups of 4 animals each and fed different diets (7.5% lard, 7.5% tuna oil, 20.0 % lard and 20.0% tuna oil). Two times a week animals were anaesthetized and injected i.p. with 100µL luciferin 15 min before the imaging session. Using the Living Image Software, photon emission was mapped for selected body areas. On day 70, animals were sacrificed after a challenge with Sodium Arsenite. Specific organs were dissected and immediately subjected to ex vivo imaging session. MIXED and GLM procedures of SAS software were used for statistical analysis. Dietary treatments did not affect body weight and feed intake as well as Nrf2 expression in both pre- and post-challenge phases, with the exception of the abdominal region (P=0.031 pre-challenge); in this area, during the pre-challenge phase, OVX showed lower Nrf2 activation (P
Keywords: nrf2; oxidative stress; reporter mice; omega-3